Inclusive democracy and its prospects - Freeman, David, (Universidad Nacional de Quilmes, 2004)
Takis Fotopoulos inclusive democracy project has generated one of the most interesting and ambitious undertakings within contemporary political philosophy. Fotopoulos synthesises what he regards as the principal contributions of five discrete traditions, retrieves classical Athens as democratic exemplar, thinks through and extrapolates the implications of his vision for daily life, and seeks to anticipate and resolve conundrums likely to follow. Any one of these dimensions would render his project noteworthy. Nonetheless, his project occurs within a historic moment that limits its prospects of consideration beyond its own political constituency. However unfairly, Fotopoulos proposals will struggle for mass attention for reasons not principally of his creation. A leading reason for this is the widespread and probably reasonable leeriness toward large-scale alternatives borne of the pathological nature of much twentieth century political radicalism.